Exercise enhances memory consolidation in the aging brain - Snigdha, Shikha; de Rivera, Christina; Milgram, Norton W.; Cotman, Carl (Frontiers in Aging Neuroscience, 2014)
Exercise has been shown to reduce age-related losses in cognitive function including learning and memory, but the mechanisms underlying this effect remain poorly understood. Memory formation occurs in stages that include an initial acquisition phase, an intermediate labile phase, and then a process of consolidation which leads to long term memory formation. An effective way to examine the mechanism by which exercise improves memory is to introduce the intervention (exercise), post-acquisition, making it possible to selectively examine memory storage and consolidation. Accordingly we evaluated the effects of post-trial exercise (10 minutes on a treadmill) on memory consolidation in aged canines both right after, an hour after, and twenty-four hours after acute exercise training in concurrent discrimination, object location memory (OLM) and novel object recognition (NOR) tasks. Our study shows that post-trial exercise facilitates memory function by improving memory consolidation in aged animals in a time-dependent manner. The improvements were significant at twenty-four hour post exercise and not right after or one hour after exercise. Aged animals were also tested following chronic exercise (10 min/day for 14 consecutive days) on OLM or till criterion were reached (for reversal learning task). We found improvements from a chronic exercise design in both the object location and reversal learning tasks. Our studies suggest that mechanisms to improve overall consolidation and cognitive function remain accessible even with progressing age and can be re-engaged by both acute and chronic exercise.